Crystallization and preliminary diffraction studies of prostaglandin E(2)-specific monoclonal antibody Fab fragment in the ligand complex - Kurahashi, Yuko (International Union of Crystallography, 2008)
Prostaglandin E(2) is a major lipid mediator that regulates diverse biological processes. To elucidate how prostaglandin E(2) is recognized specifically by its antibody, the Fab fragment of a monoclonal anti-prostaglandin E(2) antibody was prepared and its complex with prostaglandin E(2) was crystallized. The stable Fab–prostaglandin E(2) complex was prepared by gel-filtration chromatography. Crystals were obtained by the microbatch method at 277 K using polyethylene glycol 4000 as a precipitant. A diffraction data set was collected to 2.2 Å resolution. The crystals belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 70.3, b = 81.8, c = 82.2 Å. The asymmetric unit was suggested to contain one molecule of the Fab–prostaglandin E(2) complex, with a corresponding crystal volume per protein weight of 2.75 Å(3) Da(−1).